Reaching Florida Urban Opinion Leaders: Uncovering Preferred Communication Channels - Amanda Ruth; Lisa Lundy (Journal of Applied Communications, 2004)
Opinion leadership is a common concept in communication theory and research. This study examines the communication channels and sources of information that opinion leaders access for general information and specifically for agricultural information. Through a mailed survey opinion leaders’ pre-existing knowledge, attitudes, and perceptions toward agriculture were measured as well as their concern with several agricultural issues. This information was used to construct a foundation for an agricultural campaign in the state of Florida. By understanding the important issues that could make effective agricultural messages and the means for disseminating those messages, agricultural communicators can more successfully implement public relations campaigns to garner support for the agricultural industry. Survey findings suggest that opinion leaders do not have high knowledge levels about agriculture; however, they feel it is an important industry and have an interest in knowing more. The results indicate that an agricultural campaign to reach Florida urban opinion leaders should consist of a message dealing with agriculture’s role in water quality and the primary means of message dissemination should be through print media, primarily newspapers.